OCCLUSION IN NEWLY FABRICATED BRIDGE: OKLUSI PADA GIGI TIRUAN JEMBATAN YANG BARU DIBUAT - Natasya Ahmad Tarib; Marlynda Ahmad (Dentika: Dental Journal, 2009)
Fabrication of prostheses must be planned and designed to fit harmoniously with the complexity of the neuromuscularsystem of the patient, the temporomandibular joints and supporting structures of the teeth. Any occlusal interference fromthe prostheses would invade the systems and caused various problems to the patient. The aim of this study was to evaluatethe occlusion of 3-unit conventional bridges prior to cementation. All bridges that scheduled for cementation was noted.Before the occlusal examination was performed, the retainers were examined to ensure good marginal fit and haveadequate interproximal contact with adjacent teeth. Occlusal examination was performed using articulating foil with thethickness of 8Âµm, Millerâ€™s forceps and thickness gauge. From 33 bridges identified, 93.9% were qualified for occlusalexamination. Most of the retainers and pontics showed multiple high spots. From 62 retainers and 31 pontics, 213occlusal contacts were obtained, with 25.8% on cuspal inclinations, 24.4% presented with high spots on marginal ridgesand 11.7% on cuspal tips. The thickness of the high spots ranges from 0.5-3.6mm. High occlusion could be resulted fromvarious factors such as inadequate tooth preparation and lack on the usage of semiadjustable articulator. Occlusalexamination has to be performed prior to bridge cementation to ensure comfort during functioning and health of the hardand soft tissues.